2021
DOI: 10.4102/jtscm.v15i0.628
|View full text |Cite
|
Sign up to set email alerts
|

Responding to supply chain disruptions caused by the COVID-19 pandemic: A Black Swan event for omnichannel retailers

Abstract: Background: The COVID-19 pandemic has triggered unprecedented growth in digital commerce and has accelerated the digital transformation of many retailers. An unforeseen event, such as the COVID-19 pandemic, is often referred to as a ‘Black Swan’ event – being of low probability to occur but causing substantial disruptions to a supply chain. Lockdown restrictions imposed to curb the spread of coronavirus resulted in significant external and internal disruptions to retailers’ supply chains. Omnichannel retailer’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 65 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…South African supply chain members remain reluctant to share information with their supply chain partners due to unequal distribution of risks, costs and benefits (Mathu, 2019). Studies by Bothma et al (2014), KPMG (2013), Naude (2020), PWC (2016) and Weber (2021) suggest that South African 3PLs lack complete visibility into the supply chain networks in which they are involved. Global studies by the Langley (2019) and the McKinsey Global Institute (2020) support that nearly half of supply chain companies around the globe were familiar only with their immediate tier partners while they knew very little about their entire supply chain network.…”
Section: Problem Statementmentioning
confidence: 99%
“…South African supply chain members remain reluctant to share information with their supply chain partners due to unequal distribution of risks, costs and benefits (Mathu, 2019). Studies by Bothma et al (2014), KPMG (2013), Naude (2020), PWC (2016) and Weber (2021) suggest that South African 3PLs lack complete visibility into the supply chain networks in which they are involved. Global studies by the Langley (2019) and the McKinsey Global Institute (2020) support that nearly half of supply chain companies around the globe were familiar only with their immediate tier partners while they knew very little about their entire supply chain network.…”
Section: Problem Statementmentioning
confidence: 99%
“…The study revealed that cybersecurity with specific threats, the quality of information security, and the security of personal data were found as the main challenges for the resilience and the right decisions for stakeholders [26].…”
Section: Discussionmentioning
confidence: 99%
“…[24]. Knowing these aspects, the digital resilience of electronic commerce was ascertained [25], as was the importance of long-term planning, and the need for strategic skills to make the right decisions for traders [26]. Electronic commerce is a vital element in worldwide economic resilience [27] and the adoption of digitisation and digital platforms is an 'escape hatch' in the development strategy and resilience of organisations [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The transportation and import-export operations were suspended during the shutdown (Kumar & Singh, 2021). Unexpected events, like the COVID-19 pandemic, are sometimes described as "Black Swan" events because they have a low likelihood of happening but have the potential to disrupt a supply chain seriously (Weber, 2021). In discussing the socioeconomic effects of the pandemic on the global economy, Nicola et al (2020) claim that the COVID-19 pandemic has had a "Black Swan" effect on the service industry due to social exclusion, self-isolation, and lockdown measures.…”
Section: Hypothesis 1 Capital Investment Has a Positive Impact On The...mentioning
confidence: 99%